THE IMPLEMENTATION OF EPISODIC MEMORY TO EFL LEARNERS - Andi Hamzah Fansury (Publikasi dan UKI Press UKI Toraja., 2023)
Episodic memory is the memory subsystem that stores information about the episodes or events in our lives. It refers to our ability to recall personal experiences from our past. Strategy in using episodic memory according to Jensen (1998) are (1) Embed emotions in the learning. (2) We remember material best when it is structured and meaningful. (3) Attitude is important. (4) Learners remember much more when the learning is connected to a field trip, music, a disaster, a guest speaker, or a novel learning location. Episodic memory can be used as teaching method to help the students to improve their ability in writing, vocabulary, and speaking. Teaching English using episodic memory make students can more explore their critical thinking